The Development of Semi – Empirical Relationship for the Determination of the Half –Lives of Even – Even Heavy Nuclei that Emit Alpha – Particles - Ali AL-Jomaily, Firas Mohammed; Khalil Al-Hobaity, Mayan Ibraheem (Iraqi Journal of Science, 2023)
The Development of Semi – Empirical Relationship for the Determination of the Half –Lives of Even – Even Heavy Nuclei that Emit Alpha – Particles